Frequency of unjustified ambulatory referrals bases on no pertinent diagnosis sent to a third level Peruvian hospital - Lescano-Osorio, Fiorella (2023)
Objective:To determine the frequency and to describe the characteristics of unjustified ambulatory referrals based on no pertinent diagnosis done at an adult outpatient clinic of a third level Peruvian hospital. Methods: A cross-sectional study was carried-out from April to December 2019 at Hospital Cayetano Heredia. Data were extracted from REFCON with a population of 99 891 referrals. To justify the reference, a list of diagnosis that does not require referral was used. In addition, variables such as age, sex, specialty of destination, category of the health center of origin, district of origin and diagnosis of the unjustified referral. Descriptive statistics was used. Results: the frequency of unjustified referrals was 8.4%; 34.2% comprised the adult population; 65.8% were elder and 67% were female. Specialties with more unjustified referrals were cardiology, geriatrics, internal medicine, family medicine and neurology. The most common unjustified diagnosis were essential hypertension, nonspecific low back pain and headache. Conclusions:Despite of socializing a list of unjustified referral diagnosis a frequency of 8,4% remain inthis category, which is like results from two previous studies.